Using a smartphone app in the measurement of posture-related pupil center shift on centration during corneal refractive surgery - Cheng, Wenbo; Li, Li; Luo, Gang; Wang, Yan (Frontiers in Cell and Developmental Biology, 2023)
Purpose: Pupil center is an important anchor point in corneal refractive surgery, which may affect by body position. This study investigated the feasibility of using a smartphone application in measurement of posture-related pupil center shifts. Methods: Images of undilated eyes were captured for 25 participants (age: 18 to 38 years) at a distance of 40 cm in four body positions (seated, supine, right lateral, and left lateral) under controlled lighting conditions. During taking images, a smartphone application was used to guide positioning without head rotation and tilt. From the images, the location of the pupil center and pupil diameter with respect to the limbus boundary were measured. Results: According to the data obtained by the smartphone application, pupil center was located slightly nasal and superior to the limbus center in the seated position, and it shifted more nasally and superiorly (p<0.001, OD 0.54±0.11 mm, OS 0.57±0.14 mm) in the supine position. When body position switched between left and right lateral positions, the pupil centers of both eyes shifted along the direction of gravity (p<0.05), and no significant shift occurred along the longitudinal axis. Moreover, pupil constriction was observed when the body position changed from seated to supine position (p<0.001, OD 0.64±0.57mm, OS 0.63±0.58 mm). Conclusions: Posture-related pupil center shift may be larger than the error tolerance of centration in corneal refractive surgery, which might be difficult to measure by the existing instruments. An accessible application is necessary for evaluating the shift of pupil center and guiding centration during the surgery.